Popular culture : an introduction - Freccero, Carla, 1956- (New York University Press, 1999)
From Madonna and drag queens to cyberpunk and webzines, popular culture constitutes a common and thereby critical part of our lives. Yet the study of popular culture has been condemned and praised, debated and ridiculed. In Popular Culture: An Introduction, Carla Freccero reveals why we study popular culture and how it is taught in the classroom. Blending music, science fiction, and film, Freccero shows us that an informed awareness of politics, race, and sexuality is essential to any understanding of popular culture. Freccero places rap music, the Alien Trilogy and Sandra Cisneros in the context of postcolonialism, identity politics, and technoculture to show students how they can draw on their already existing literacies and on the cultures they know in order to think critically.Complete with a glossary of useful terms, a sample syllabus and extensive bibliography, this book is the concise introduction to the study of popular culture.